Sexuality and relationship education training to primary and secondary school teachers: an evaluation of provision in Western Australia - Burns, Sharyn; Hendriks, J. (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group This paper describes the formative, process and short term impact evaluation of sexuality and relationships education (SRE) training for teachers in Western Australia (WA) over a three year period. The training represents one component of a broader project, the aims of which are to improve teacher’s confidence and skills in delivering SRE, and to support schools to implement effective comprehensive SRE. Formative evaluation conducted prior to the development of the training, found although most respondents were relatively confident and skilled in facilitating SRE, the need for ongoing professional development was highlighted, especially in areas such as gender diversity, pornography, sexting, violence and working with specific groups. Training focusing on the new Australian Health and Physical Education curriculum and mandatory assessment was identified as a need. Workshop evaluation found statistically significant improvements in attitudes towards SRE and increased comfort in teaching SRE, facilitating discussion and facilitating skills and activities, after the workshop. The evaluation identified the need for an integrated and coordinated whole school approach and efforts to engage teachers with lower levels of confidence in teaching SRE. Changes to the Australian Curriculum provide opportunities to enhance the development of SRE in schools. Longer-term impact evaluation is required to identify whole school changes.